Asphalt material characterization, accelerated testing, and construction management : selected papers from the 2009 GeoHunan International Conference, August 3-6, 2009, Changsha, Hunan, China - Walubita, Lubinda F. (Geotechnical special publication ;, 2009)
"This publication will be valuable to geotechnical professors and students, construction managers, and those involved in geotechnical and pavement engineering."--Jacket.